A implementação com articulação burocrática: políticas de transferência condicionada de renda no Brasil e México - Andrade, Fábio Pereira de (2016)
This thesis analyzed the bureaucracy of PTCs in Brazil and Mexico; specifically aimed to show the influence of the articulator bureaucrat (BA) on the difference in the results of targeting, taking as reference the exclusion errors estimated for both programs. The analyzed incorporated articulation in intergovernmental and intersectoral dimensions in the implementation of strings defined for both programs, considering the period 2003-2010, in which both BAs faced the challenge of expanding the program's coverage and keep targeting index. This study was guided by the qualitative approach, through the comparison case study from which it was possible to interpret that the best targeting outcomes relate to the ability to access administrative features (federal and municipal) of the Brazilian bureaucrat. Theoretically, the use of Goggin et al (1990) model helped the weighting variables involved in determining the results of individual cases